Growth in the Dominican Republic and Haiti : Why has the Grass Been Greener on One Side of Hispaniola? - Jaramillo, Laura (IMF Working Papers; Working Paper ;, 2007)
The Dominican Republic and Haiti share the island of Hispaniola and are broadly similar in terms of geography and historical institutions, yet their growth performance has diverged remarkably. The countries had the same per capita real GDP in 1960 but, by 2005, the Dominican Republic's per capita real GDP had tripled whereas that of Haiti had halved. Drawing on the growth literature, the paper explains this divergence through a combined approach that includes a panel regression to study growth determinants across a broad group of countries, and a case study framework to better understand the specific policy decisions and external conditions that have shaped economic outcomes in the Dominican Republic and Haiti. The paper finds that initial conditions cannot fully explain the growth divergence, but rather policy decisions have played a central role in the growth trends of the two countries. This Working Paper should not be reported as representing the views of the IMF. The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate.